A Lublin survivor : life is like a dream - Eisenkeit, Eva, 1919- (Sussex Academic Press, 2019)
""To this day I am unable to understand how I managed to survive against all odds." So relates the memoir of a young woman, Eva Szek (later Eisenkeit), who survived the Nazi onslaught against Jews in her beloved city of Lublin in Poland, an important centre of Jewish religion and culture. Eva recounts with compelling testimony her fearless fight not to fall into German hands and to save her family. Her experiences under German occupation, her struggle to survive and her subsequent liberation is an historical account of the tragedy of a Jewish community destroyed. The memoir describes Jewish Lublin life before the war, its religious institutions and charities; Polish-Jewish relations; the German bombing and invasion; the Russian escape options; the German occupation and registration of Jews; Eva's escape from the ghetto and two labour camps; her hiding in villages and farms, and complex wartime relations with Poles; her negotiated freedom with Mr. X (a Polish man who hid Jews for money, and cannot be considered a "Righteous"; life in liberated Lublin, including the first Passover celebration; meeting other survivors and trying to make a living; and Eva's postwar move to Lodz and marriage, and then to a Displaced Persons (DP) camp in Germany. As her eighty-fifth birthday approached, Eva asked her daughter Esther to take down her life story "so the whole world will know what the Germans did." A Lublin Survivor: Life is Like a Dream not only provides an extraordinarily complete and descriptive picture of life in pre-war and liberated Lublin but a first-hand account of the obliteration of its Jewish community and one individual's indomitable determination to survive against all odds"--